Limit Cycles in a Cubic Kolmogorov System with Harvest and Two Positive Equilibrium Points - Qi-Ming Zhang; Feng Li; Yulin Zhao (Abstract and Applied Analysis)
A class of planar cubic Kolmogorov systems with harvest and two positive equilibrium points is investigated. With the help of computer algebra system MATHEMATICA, we prove that five limit cycles can be bifurcated simultaneously from the two critical points (1, 1) and (2, 2), respectively, in the first quadrant. Moreover, the necessary conditions of centers are obtained.